Sosialisasi Tentang Pentingnya Hak Kekayaan Intelektual Bagi UMKM - Pangastuti, Ria Lestari; Triwidyati, Endang; Kristanti, Desi (LPPM Universitas Bumigora, 2023)
MSMEs in Indonesia are predicted to be the biggest pillars of the economy. This can be seen from the significant emergence of new MSME actors in Indonesia. In 2022, the East Java Representative projects that East Java's economic growth in 2022 can be boosted to reach 5 percent - 5.8 percent through a number of efforts to increase economic sectors, one of which is MSMEs. [1]. Of the 64.1 million MSME actors in Indonesia, only 10,632 are managing their trademarks, this phenomenon occurs due to the lack of awareness of MSME actors on intellectual property rights. Meanwhile, for the management of IPR, many conveniences have been provided, including the bus registering IPR via online by fulfilling the requirements that have been applied by the Directorate General of Intellectual Property Rights. The problems that occur are: 1. MSME actors have very low knowledge of HKI, 2. MSME actors do not know the benefits of HKI for their business, 3. MSME actors do not know the procedure for registering IPR. The benefits of HKI protect their work with HKI